Students’ Perceptions about Debate and Their Ability to Debate - Juliansyah, Juliansyah; Adi, Bambang Trisno; Beressaby, Rheinatus Alfonsus (Universitas Pahlawan Tuanku Tambusai, 2023)
This is a research of correlation study that aims to find the level of relationship between the ability to debate (in English) of the students of English Language and Culture Department at Darma Persada University and their perception of debating. The relationship is measured based on 3 variables, namely: 1) the students’ knowledge about debating, 2) the students’ self confidence in debating, and 3) the teaching process the students have to improve the debating skill. This study involves 75 students from 3 different classes. The students first went through a learning process about the concept of debating. Then they practiced debating. The students’ perception was measured through a research instrument in the form of a questionnaire, while the relationship values were taken from the scores obtained after students carried out tests in the form of debating. The result of this research indicates that the score for the correlation coefficient between the students’ ability in debating and the students’ knowledge on the definition on debating and technical ability on debating is 0.195. This means positive correlation between the variables. Secondly, in term of students’ self-confidence, the data analysis results a positive correlation coefficient between the students’ ability in debating and the students’ self-confidence. The score is 0.195 meaning a positive correlation. Lastly, in term of the teaching process in the course related to debate, the correlation coefficient is considerably high; 0.222. This means that the students have very positive attitude on the course.